Perancangan Sistem Informasi Penjualan Obat Pada Apotik Poliklinik Rumah Sakit Fatmawati - Gunita, Maya (Jurnal Gemaedu, 2018)
Drug sales at the Fatmawati Hospital Polyclinic Pharmacies have accumulated queues of people buying drugs. The process of purchasing drugs is often an error caused by the system is still manual, the process of checking drugs and drug prices, late messages when the stock of thinning drugs, this is due to knowing the stock of drugs should be checked directly and the information submitted to the pharmacist's head is limited to drugs sold. The pharmacist assistant should look at the drug list book to find the medication that the patient is asking for or not, so in the process of purchasing the drug there is often a data error and in the process of checking the stock of the drug is still manual takes a long time. The author provides problem-solving solutions with the use of computer technology as a tool to process the required data in the form of files or in other words the use of computer-based data processing system with the application program (computerization). Some of the advantages of using a computerized system are to reduce the occurrence of queue buildup due to faster service, faster and more accurate information presentation, better data storage and smaller error factors or rarely occur because the process does not need to be repeated, in case of error simply edit the data. The proposed system is expected to be applied so that queuing can be avoided and may facilitate Pharmacist access to know the progress of the Pharmacy